The significance of ramakrishna’s religious and philos ophical doctrine - Кокеевa, Д. М. (Journal of Oriental Studies, 2018)
The article deals with the theoretical aspects of the life and the conclusions of the religious and philosophical doctrines of modern Indian educator for Europeans, genius, Ramakrishna, who was calling to compromise the different currents of Hinduism in the Indian society, recognized as a restorer of ancient Indian religions. At the same time, it analyzes the teachings of Bhagavan Sri Ramakrishna perceiving all people the same and calling them to one religion, which refers to the Vedic tradition in early Indian religion, and tells that he is the founder of bhakti-yoga and religious philosophy teacher.